POPULATION OF THE Be STARS IN THE YOUNG OPENCLUSTERS - Malchenko, S. L. (Одеські астрономічні публікації, 2008)
Both high and medium resolution spectroscopy of the Be stars and binary stellar systems in the young open clusters (e.g., NGC 869 & 884, NGC 6913, NGC 6871, NGC 7160 and NGC 7419) were carried out. High resolution spectroscopy of 100 stars in the Hα region and 42 stars in the region of 4400-4960 Å with the medium resolution were obtained. The spectra of 52 B and 48 Be stars were studied. Teff, log g and V sini were determined by using the medium resolution spectra. One new Be star was found, one star showed complex variability of the Hα line profile, which is characterized as a close binary system. A few demonstrate long - term V/R variability of the emission peaks that can be easy described by the one arm oscillations in theirs envelopes. Our clusters survey approved that classical Be stars mostly appeared at age of 10 Myr, and reached the maximum abundance in the age of interval 12-20 Myr.